2021
DOI: 10.1111/eci.13683
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxal‐5‐phosphate induced cardioprotection in aging associated with up‐expression of cystathionine‐γ‐lyase, 3‐mercaptopyruvate sulfurtransferase, and ATP‐sensitive potassium channels

Abstract: Background:In the present work, we investigated the cardioprotective potential of pyridoxal-5-phosphate (PLP) in old rats as a cofactor of enzymes that synthesize hydrogen sulphide (H 2 S). Materials and methods:PLP was administered per os in a dose of 0.7 mg per kg daily for 2 weeks. Rats were divided into three groups (adult, old and old +PLP) of 20 animals. The cardiac mRNA levels of genes encoding H 2 S-synthesizing enzymes cystathionine-γ-lyase (CSE) and 3-mercaptopyruvate sulfurtransferase (3-MST), uncou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…13,14,21 We recently showed that PLP administration in old rats was associated with an increased expression of H 2 S-synthesizing enzymes CSE and 3-MST, increased levels of hydrogen sulphide in the heart tissue, and prevented reperfusion dysfunction of the heart in ischemia-reperfusion. 10 In this study, 3-MST and CSE expression was significantly increased in old exercise-trained rats, and endogenous hydrogen sulphide production in cardiac tissue and cardiac mitochondria was restored to the level of adult untrained animals (Figures 1,2). Similar results with increased expression of 3-MST and CSE and H 2 S levels in old rats during training were obtained by Ma et al 22 The effects of physical training on pore formation in the mitochondria of the heart of old rats were manifested in a decrease in the amplitude of organelle swelling both in calcium-free medium and under the action of the inducer (10 −4 moL/L), as shown in Figure 3B.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…13,14,21 We recently showed that PLP administration in old rats was associated with an increased expression of H 2 S-synthesizing enzymes CSE and 3-MST, increased levels of hydrogen sulphide in the heart tissue, and prevented reperfusion dysfunction of the heart in ischemia-reperfusion. 10 In this study, 3-MST and CSE expression was significantly increased in old exercise-trained rats, and endogenous hydrogen sulphide production in cardiac tissue and cardiac mitochondria was restored to the level of adult untrained animals (Figures 1,2). Similar results with increased expression of 3-MST and CSE and H 2 S levels in old rats during training were obtained by Ma et al 22 The effects of physical training on pore formation in the mitochondria of the heart of old rats were manifested in a decrease in the amplitude of organelle swelling both in calcium-free medium and under the action of the inducer (10 −4 moL/L), as shown in Figure 3B.…”
Section: Discussionsupporting
confidence: 51%
“…In particular, we have shown the inhibition of mPTP formation in experiments on suspensions mitochondria and the associated reduction in the processes of necrosis and apoptosis in anoxia‐reoxygenation of neonatal cardiomyocytes by pharmacological activators of K ATP channels flocalin and tioflocalin 6,9 . In a series of experiments involving cofactor H 2 S‐synthesizing enzymes pyridoxal‐5‐phosphate and hydrogen sulfide donor NaHS at reduced levels of endogenous H 2 S production in the heart of old rats, we observed increased hydrogen sulfide levels, reduced oxidative stress, and better recovery of function of the ischemic heart during reperfusion that proves the important role of this gaseous transmitter in the regulation of mitochondrial function 5,10 . H 2 S is an important endogenously synthesized signaling molecule synthesized by three enzymes, two of which have a pronounced expression in the cardiovascular system, namely 3‐mercaptopyruvate sulfurtransferase (3‐MST), which is localized mainly in mitochondria, where it functions together with cysteine aminotransferase (CAT) and cystathionine‐γ‐lyase (CSE) in the cytosol of cells 11 .…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Some of the most obvious approaches to achieve this goal may involve exercise—which is known to counteract aging-associated decline in 3-MST mRNA expression in the heart [ 49 ]—or various dietary interventions, including various intermittent fasting or other dietary restriction approaches [ 39 , 46 ]. Betaine, [ 55 ] as well as pyridoxal-5-phosphate [ 56 ], has also been recently shown to upregulate 3-MST expression in the brain and heart of rodents, respectively. There may be also pharmacological possibilities for a redox-based “reactivation” of 3-MST [ 53 , 54 , 57 ].…”
Section: Perspectivesmentioning
confidence: 99%